Epidemiological, clinical, and molecular analysis of human adenovirus infections in hospitalized children with acute respiratory infections in Tianjin, China - Yulian Fang; Yulian Fang; Min Lei; Min Lei; Lu Zhang; Mengzhu Hou; Mengzhu Hou; Ning Wang; Ning Wang; Chunquan Cai; Chunquan Cai (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHuman Adenovirus (HAdV) is a significant pathogen for acute respiratory infections(ARIs) in children. However, its epidemiological patterns, serotype distribution changes, and molecular mechanisms associated with severe pneumonia during and after the COVID-19 pandemic require further elucidation through large-scale and molecular typing studies.MethodsThis study used a retrospective cohort design to analyze 28060 respiratory specimens from Tianjin Children’s Hospital from March 2022 to March 2024. HAdV detection and typing were performed through targeted high-throughput sequencing and PCR-based amplification of Penton, Hexon, and Fiber genes for phylogenetic analysis. Additionally, clinical data were compared to assess differences in clinical presentations among pediatric patients infected with different HAdV types.ResultsThe overall HAdV detection rate was 8.9% (2,484/28,060), with significant male predominance (9.2% vs. 8.4%, P = 0.019) and age-specific susceptibility peaking in school-aged children (10.4%, P < 0.001). Seasonal patterns demonstrated winter predominance (15.9%), contrasting with other seasons (P < 0.001). Genotyping of 1,914 positive specimens demonstrated HAdV-3 dominance (53.4%, 1,022), followed by HAdV-7 (17.7%, 338), HAdV-2 (8.4%, 160), HAdV-1 (7.9%, 152), and HAdV-21 (6.4%, 122). The diagnosis mainly included pneumonia, bronchitis, adenopharyngitis, and upper respiratory tract infections (URTIs). Genotype-clinical correlations showed distinct patterns: HAdV-3 (55.6%) and HAdV-7 (20.9%) predominated in pneumonia cases, with HAdV-7 linked to severe pneumonia (P<0.001). HAdV-3 (40.6%) and HAdV-2 (16.7%) were more common in adenopharyngitis, while HAdV-3 and HAdV-21 were more common in bronchitis (51.2% and 11.1%) and URTIs (31.9% and 19.1%). Molecular characterization revealed structural conservation in the Penton protein of HAdV-C and identified Hexon as the most polymorphic region with 85 variable sites, indicating divergent evolutionary pressures across viral domains.ConclusionHAdV-3, HAdV-7, HAdV-2, and HAdV-1 were the predominant HAdV types in children hospitalized with ARIs in Tianjin. Moreover, not only the epidemiological characteristics of different HAdV types vary, but there are also certain differences in the clinical symptoms and outcomes of children infected with different types of HAdV. Therefore, it is essential to differentiate HAdV types for epidemiological surveillance and clinical management purposes.